1998
DOI: 10.1210/endo.139.4.5889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leptin on Corticotropin-Releasing Factor (CRF) Synthesis and CRF Neuron Activation in the Paraventricular Hypothalamic Nucleus of Obese (ob/ob) Mice

Abstract: The effects of leptin on the levels of CRF messenger RNA (mRNA) in the paraventricular hypothalamic nucleus (PVN), on the activation of the PVN CRF cells, and on the plasma levels of corticosterone were investigated in lean (+/?) and obese (ob/ob) C57BL/6J male mice. Murine leptin was s.c. infused using osmotic minipumps. The treatment period extended to 7 days, and the daily dose of leptin delivered was 100 microg/kg. The mice were killed either in a fed state or following 24 h of total food deprivation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(78 citation statements)
references
References 49 publications
9
65
1
3
Order By: Relevance
“…For example, leptin treatment blocks elevation of ACTH and corticosterone levels following restraint [46] and ether stress [47]. Furthermore, leptin decreases mRNA expression of CRH in the PVN [47][48][49] and CRH release from the hypothalamus [50]. These findings suggest that the inhibitory effect of leptin on ACTH and corticosterone is probably mediated by hypothalamic CRH.…”
Section: Impact Of Leptin On Hpamentioning
confidence: 92%
“…For example, leptin treatment blocks elevation of ACTH and corticosterone levels following restraint [46] and ether stress [47]. Furthermore, leptin decreases mRNA expression of CRH in the PVN [47][48][49] and CRH release from the hypothalamus [50]. These findings suggest that the inhibitory effect of leptin on ACTH and corticosterone is probably mediated by hypothalamic CRH.…”
Section: Impact Of Leptin On Hpamentioning
confidence: 92%
“…Lu et al, 2006). In response to stressful events, leptin suppresses CRH, ACTH, and corticosterone secretion, suggesting a direct impact of leptin on the HPA axis (Ahima et al, 1996;Heiman et al, 1997;Huang et al, 1998). In addition, leptin-deficient ob/ob mice display altered Slc6a4 expression (Collin et al, 2000), decreased neuronal and glial cells, and reduced brain weight and cortical volume (Ahima 1999, Stepan 1999, further supporting the role of leptin in MDD.…”
Section: Metabolic Alterationsmentioning
confidence: 96%
“…Additionally, insulin regulates monoamine uptake and metabolism, phosphoinositol turnover, as well as norepinephrine and dopamine transporter mRNA levels (Craft & Watson, 2004). It has been shown that insulin can recruit GABA receptors (Wan et al, 1997) and promote internalization ofamino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) receptors, which suggests that insulin plays a critical role in neuronal signaling and synaptic plasticity (Huang et al, 1998). Interestingly, brain volume abnormalities and neurocognitive deficits commonly found in MDD patients have been observed in individuals with diabetes mellitus (DM), suggesting overlapping pathophysiology between MDD and DM (McIntyre et al, 2010).…”
Section: Metabolic Alterationsmentioning
confidence: 99%
“…Consistent with this view are results showing that CRH mRNA expression within the hypophysiotropic neurons is not decreased in unrestrictedly fed obese faafa Zucker rats and obaob mice and is even induced in these rodents following food deprivation. 41,46 In addition, recent studies have shown that leptin can blunt the synthesis of CRH within the PVH. Leptin has for instance been reported to block both the CRH synthesis induced by food deprivation in obese obaob mice 46 and the CRH secretion from isolated rat hypothalami stimulated by glucose deprivation.…”
Section: Hypophysiotropic Crh Neurons and The Regulation Of Energy Bamentioning
confidence: 99%